2021
DOI: 10.3389/fgene.2021.667724
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0124644 Serves as a ceRNA for miR-590-3p to Promote Hypoxia-Induced Cardiomyocytes Injury via Regulating SOX4

Abstract: Circular RNA (circRNA) is an important factor for regulating the progression of many cardiovascular diseases, including acute myocardial infarction (AMI). However, the role of circ_0124644 in AMI progression remains unclear. Hypoxia was used to induce cardiomyocytes injury. The expression of circ_0124644, microRNA (miR)-590-3p, and SRY-box transcription factor 4 (SOX4) mRNA was measured by qRT-PCR. Cell counting kit 8 (CCK8) assay and flow cytometry were utilized to detect cell viability, cell cycle progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Circ_ROBO2 has been reported to promote ox-LDL-mediated endothelial injury in human vascular endothelial cells [ 32 ]. Moreover, circ_ROBO2 promoted hypoxia-induced cardiomyocytes damage via regulation of miR-590-3p/SOX4 axis [ 33 ]. In addition, circ_ROBO2 knockdown inhibited the proliferation and migration in PDGF-BB-treated human aortic smooth muscle cells [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Circ_ROBO2 has been reported to promote ox-LDL-mediated endothelial injury in human vascular endothelial cells [ 32 ]. Moreover, circ_ROBO2 promoted hypoxia-induced cardiomyocytes damage via regulation of miR-590-3p/SOX4 axis [ 33 ]. In addition, circ_ROBO2 knockdown inhibited the proliferation and migration in PDGF-BB-treated human aortic smooth muscle cells [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of circ_0124644 attenuates hypoxia-induced cardiomyocyte injury, such as by suppressing apoptosis and oxidative stress and inhibiting AMI progression through the circ_0124644/miR-590-3p/SOX4 axis. 107 In addition, it was demonstrated that knockdown of circROBO2 alleviates hypoxia-induced cardiomyocyte injury and apoptosis and improves cardiac dysfunction by modulating the circROBO2/miR-1184/TNFR1-associated death domain protein (TRADD) axis. 108 Finally, Wu et al.…”
Section: Circrnas and Cardiomyocyte Apoptosismentioning
confidence: 99%
“…circ_0124644 was demonstrated to be a diagnostic biomarker for CAD, including MI, because it is easily detected in peripheral blood with high specificity and sensitivity and because its expression is upregulated in serum samples from AMI patients, suggesting that its diagnostic value would be greater when combined with circ_0098964. 107 , 146 Li et al. 132 proposed that the circPAN3/miR-221/Foxo3/ATG7 axis, a strong predictor of cardiac fibrosis during MI, may serve as a sensitive biomarker for cardiac fibrosis during MI.…”
Section: Circrnas As Diagnostic and Prognostic Biomarkers For MImentioning
confidence: 99%
See 2 more Smart Citations